Planktonic algal blooms from 2000 to 2015 in Acapulco Bay, Guerrero, Mexico - Meave del Castillo, Maria Esther A.; Zamudio Resendiz, María Eugenia (Instituto de Ecología, A.C., 2018)
Background and Aims: Harmful algal blooms (HABs) affect the marine ecosystem in multiple ways. The objective was to document the species that produced blooms in Acapulco Bay over a 15-year period (2000-2015) and analyze the presence of these events with El Niño-Southern Oscillation (ENSO).Methods: Thirty-five collections, made during the years 2000, 2002-2004, 2006-2011, 2013-2015, were undertaken with phytoplankton nets and Van Dorn bottle, yielding 526 samples, of which 423 were quantified using the Utermöhl method. The relationship of HAB with ENSO was made with standardized values of Multivariate ENSO Index (MEI) and the significance was evaluated with the method quadrant sums of Olmstead-Tukey.Key results: Using data of cell density and high relative abundance (>60%), 53 blooms were recorded, most of them occurring during the rainy season (June-October) and dry-cold season (November-March), plus 37 blooms reported by other authors. These 90 blooms were composed of 40 taxa: 21 diatoms and 19 dinoflagellates, the former mostly innocuous. Sixty-seven blooms had species reported as noxious, of which 11 species commonly produce toxic HAB. Toxic taxa are Pseudo-nitzschia spp. (four taxa), and seven dinoflagellates.Conclusions: Abundance analyses of Pyrodinium bahamense var. compressum and Gymnodinium catenatum against values of MEI showed a clear tendency to produce HAB in La Niña conditions. Both taxa, producers of saxitoxins, cause paralytic shellfish poisoning (PSP) and coexist in Acapulco; therefore, they present a risk to human health. Another noxious 52 taxa found in Acapulco were currently considered potential HABs, because they have been recorded at low densities. Given the sharp differences in density values of bloom-forming species found in this work compared to those reported by other authors on similar dates, it is important to perform calibration tests to rule out possible errors in cell counts.